Gastronomy and Tourism Development: a systematic literature review (Research, Society and Development, 2020)
This article aims to verify and analyze the scientific production regarding the role of gastronomy in the tourist development of the destination. For that, studies were selected from the Scopus database through the combination of keywords "gastronomy" and "development" and "tourism". As a result, 104 documents were found, and these were selected based on the title, abstract reading, objectives, methodologies, and for being relevant and coherent in approach to the researched topic, integrating a set of 21 studies. The works were analyzed using the Systematic Literature Review methodology, with a quantitative and qualitative approach to the data. It is concluded that it is necessary to value the combination of gastronomy and tourism development, in order to offer a product that fits the tourist consumer, being effective to meet the needs of the contemporary consumer.